Effect of crumb rubber and nano silica on the fatigue performance of roller compacted concrete pavement - Adamu, M. (Cogent OA, 2018)
Roller compacted concrete (RCC) pavement is subjected to continues traffic loading from vehicular activities which can results to fatigue cracking. Fatigue is one of the commonest defects affecting pavement which affect the cost of maintenance, and shortens pavement design life. To carter for these factors, higher deformation resistant pavements with longer design life need to be designed. Therefore, in this study, crumb rubber was used as a partial replacement to fine aggregate in RCC pavement to improve its fatigue life. Five mixtures were considered; one control mixture, two mixtures with fine aggregate replaced using crumb rubber at 10 and 20 by volume; one mixture containing 20 crumb rubber as partial replacement to fine aggregate 1 nano silica added by weight of cementitious materials. Lastly, one high volume fly ash (HVFA) RCC pavement mixture where 50 cement was replaced with fly ash, and 20 fine aggregate replaced with crumb rubber. The results showed that both crumb rubber and nano silica increases the bending resistance and fatigue life of RCC pavement. While HVFA decreases both flexural strength and fatigue performance of RCC pavement. The double logarithmic-equation can best be used to determine the stress levelânumber of cycles (SâN) fatigue behavior and relation for RCC pavement mixtures. Â© 2018 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.